A certain subclass of analytic functions associated with the quasi-subordination - ARJOMANDINIA, Parviz; RAHIMPOOR, Hossein (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
In the present paper we study quasi-subordination under a multivalent function and we consider a certain subclass of (normalized) analytic functions based on quasi-subordination. Applications and consequences of the main results are also cosidered which some of them extend the earlier issues. Mathematics Subject Classification (2010): 30C45, 30C80.